Re-Desain Interior Sekolah Dasar Kristen Petra 1 Berbasis Multiple Intelligences di Surabaya - Jessica Fideline Sidharta; Hedy Constancia Indrani; Purnama Esa Dora Tedjokoesomo (Intra, 2018)
The education pattern in kindergarten is different from elementary levels. Children at the elementary level begin to understand about differences and the environment. They have more potential to grow and absorb new information. The elementary school system in Indonesia, especially in Surabaya, is often limited to facilitate children's academic intelligence and not facilitate non-academic intelligence. Almost all elementary schools in Surabaya do not pay attention to the student various learning styles that cause students often do not understand lessons taught during the class. Student's low score then considered as